PEMANFAATAN INVENTORI MINAT DALAM LAYANAN BIMBINGAN KARIR DI MAN ASAHAN - Liza Ulmi Widi Arnaz; Alfi Rahmi (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
This study aims to look at the implementation of career guidance services by utilizing interest inventories at MAN Asahan. Planning for further studies for a course is not an easy thing for students to decide considering it supports their future life. They will have difficulties in determining a career, for example in terms of information, doubts about their own interests, as well as input from their parents and surroundings. Students need direction and guidance from the guidance and counseling teacher at school, in order to gain understanding and be able to make future career decisions. Therefore, it is necessary to implement career guidance by utilizing an interest inventory. This interest inventory will later be used as reference material for students in understanding their own interests. This research is a type of descriptive research with observation and interview methods. The results of the implementation of career guidance by utilizing interest inventories at MAN Asahan make it easier for students to understand the direction of their interests and obtain more accurate information about their interests associated with the study program that students will choose later. The obstacle faced in the implementation of this career guidance is the lack of time that can be used considering that this service is carried out on the sidelines of study time so that the implementation is not optimal, however this is different from students who take the initiative themselves to go to the counseling teacher to carry out career guidance services at the right time. after school or during free hours.